The Brunnsviken Brief Quality of Life Scale (BBQ): Development and Psychometric Evaluation. Issue 3 (3rd May 2016) - Lindner, Philip; Frykheden, Ola; Forsström, David; Andersson, Erik; Ljótsson, Brjánn; Hedman, Erik; Andersson, Gerhard; Carlbring, Per
Abstract: Measurements of subjective quality of life (QoL) are an important complement to symptom ratings in clinical research and practice. Despite there being several established QoL self-rating scales, we identified a need for a freely accessible, easy-to-use inventory, validated for use with both clinical and non-clinical samples, based on the overall life satisfaction conceptualization of QoL. The Brunnsviken Brief Quality of life scale (BBQ) was designed to meet these requirements. Items were selected by performing a factor analysis on a large data-set of QoL ratings collected previously. Six life areas (Leisure time, View on life, Creativity, Learning, Friends and Friendship, and View of self) were identified as important for overall QoL and were included in the BBQ. A psychometric evaluation was performed using two independent samples: healthy undergraduate students ( n = 163), and a sample seeking treatment for social anxiety disorder ( n = 568). Results suggested a unifactorial structure, with good concurrent and convergent validity, high internal and test-retest reliability, and accurate classification ability. We conclude that the BBQ is a valid and reliable measure of subjective QoL for use in clinical and research settings. The BBQ is presently available in 31 languages and can be freely downloaded fromwww.bbqscale.com .